First experimental results obtained using the highpower free electron laser at the siberian center for photochemical research - Antokhin, E.A.; Akberdin, R.R.; Arbuzov, V.S.; Bokov, M.A.; Bolotin, V.P.; Burenkov, D.B.; Bushuev, A.A.; Veremeenko, V.F; Vinokurov, N.A.; Vobly, P.D.; Gavrilov, N.G.; Gorniker, E.I; et al. (Вопросы атомной науки и техники, 2004)
The first lasing near the wavelength of 140 µm was achieved in April 2003 using a high-power free electron laser (FEL) constructed at the Siberian Center for Photochemical Research. In this paper we briefly describe the design of the FEL driven by an accelerator–recuperator. Characteristics of the electron beam and terahertz laser radiation, obtained in the first experiments, are also presented in the paper.